Why there and then, not here and now? Ecological offsetting in California and England, and the sharpening contradictions of neoliberal natures. (September 2019) - Lockhart, Andy; Rea, Chris
Failure has become an increasingly important theme of debate in the literature on neoliberal natures. In this article we take up this topic with respect to ecological offsetting, often regarded as an exemplar of market-oriented conservation. Comparing the case of species banking which emerged in California in the 1990s with frustrated efforts to implement a biodiversity offsetting programme in England beginning in 2010, we develop a novel analytical framework for explaining why this kind of environmental market-making may or may not be successful in different contexts. Drawing on work in geography on the neoliberalisation of nature and insights from economic sociology, we characterise ecological offsetting as 'command-and-commodify' regulation: a peculiar form of hybrid ecological regulation which depends on an institutional mix of 'authoritative' and 'economic' power to function. In California, these kinds of environmental markets initially emerged at a moment of compromise, contingent on an embrace of 'market' solutions to environmental problems on the one hand, and a somewhat paradoxical expansion of authoritative power to ecologically regulate land development, on the other. In England, by contrast, deep fiscal austerity and deregulatory zeal, combined with resistance from nearly every quarter, initially undermined the possibility of balancing economic and authoritative power, which we argue is necessary for the construction of viable ecological offsetting. Reflecting on themes in the wider literature, we conclude by questioning whether the English experience is indicative of sharpening tensions between economy and ecology in the late neoliberal era.